Analisis Klasifikasi K-Means Terhadap Pemahaman Konsep dan Self-Efficacy: Menjelajahi Hubungan dalam Konteks Pendidikan - Magdalena Wangge; Dadan Dasari; Turmudi Turmudi (Department of Mathematics, Hasanuddin University, 2024)
Concept understanding and self-efficacy are two important aspects of mathematics learning that are interrelated. However, there is still debate about the relationship between these two aspects in the context of mathematics learning. Therefore, this study was conducted to analyze the classification of concept understanding and self-efficacy using K-means clustering with a sample of grade VIII students from three selected schools in Wolowaru District and Kelimutu District, Ende Regency, NTT. Data were collected through concept understanding test and self-efficacy questionnaire. The results showed that students' concept understanding and self-efficacy belonged to the medium and low classes. However, there was a practically insignificant correlation between the two aspects. The implication is the importance of developing learning strategies that can improve students' concept understanding and self-efficacy in the context of mathematics education.